056. Impacted CBD Stones in Ampula Vater Evacuated by Transduodenal Approach in A 48-year-old Patient at Prof. Dr. IGNG Ngoerah Hospital in 2024 - Wijaya, Komang Soni Wicaksana; Sueta, Made Agus Dwianthara (JBN (Jurnal Bedah Nasional), 2024)
Background : Cholecystolithiasis and choledocholithiasis are common biliary disorders that can lead to significant complications if left untreated. Among these complications, the formation of impacted CBD stones, particularly at the Ampulla of Vater, poses a unique clinical challenge. The Ampulla of Vater is the anatomical site where the common bile duct (CBD) and pancreatic duct converge, and its obstruction can lead to biliary colic, cholangitis, or pancreatitis. Urgent stone removal is critical for improving the patient’s condition. Case : A 48-year-old male patient presents to the emergency department with right upper abdominal pain since 10 days ago accompanied with icteric sclera since 10 days ago. There was nausea and vomiting when eating high-fat foods. The stools were brownish in color, the urine color was similar to tea color. The patient regularly takes UDCA 3 x 250 mg IO, simvastatin 1 x 20mg IO, curcuma 3 x1 tab IO, lansoprazole 2 x 30mg IO. Physical examination showed icteric eyes, jaundice, liver enlargement 2 fingers below costae arch with positive Murphy's sign. Complete blood examination showed leukocytosis, decreased hemoglobin, hypokalemia, as well as increased direct bilirubin, total bilirubin, and indirect bilirubin. BOF result showed sentinel loop on the right umbilical region suspected inflammatory process. MRI impression of choledocholithiasis causing dilatation of EHBD and IHBD proximal aspect without signs of cholangitis, hepatomegaly, simple cyst of left kidney (Bosniak I). Abdominal ultrasound with the conclusion of cholecystitis with dilatation and thickening of the ductus cysticus wall suspicious of inflammation, dilatation of the right and left IHBD, common hepatic duct, to the proximal common biliary duct, the presence of distal obstruction cannot be evaluated because it is covered by intestinal shadows, mild prostatic hypertrophy accompanied by prostate calcification. After Cholecystectomy and Explore CBD transduodenal, the patient was placed with thoracic drain with good outcome. Conclusion: The transduodenal approach to evacuating impacted CBD stones at the Ampulla of Vater is a valuable technique that can yield excellent outcomes in select cases. This case report underscores the importance of a tailored approach based on individual patient anatomy and stone characteristics.